The reputation of underwriters: A test of the bonding hypothesis - Loureiro, Gilberto (Journal of Corporate Finance, 2010)
In the spirit of the Bonding Hypothesis proposed by Stulz (1999) and Coffee (1999, 2002), I find that foreign firms that cross-list in the U.S. and undertake IPOs are more likely to employ reputable underwriters if the firms come from countries with poor shareholder protection. The additional monitoring provided by reputable underwriters may help overcome the skepticism of U.S. investors, and partially explains the higher valuation these firms obtain after the offering. There is, however, a price to pay for this bonding benefit. I find that issuers from countries with weaker shareholder protection tend to be more underpriced if they are sponsored by prestigious underwriters.